2022
DOI: 10.3390/ijgi11010057
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Effects of Multimodal Public Facilities Accessibility on Housing Prices Based on MGWR: A Case Study of Wuhan, China

Abstract: The layout of public service facilities and their accessibility are important factors affecting spatial justice. Previous studies have verified the positive influence of public facilities accessibility on house prices; however, the spatial scale of the impact of various public facilities accessibility on house prices is not yet clear. This study takes transportation analysis zone of Wuhan city as the spatial unit, measure the public facilities accessibility of schools, hospitals, green space, and public transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 47 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…It concluded that hospitals have a positive influence on the price of surrounding houses. Liu et al (2022) compared the multi-scale effects of accessibility to various facilities on housing prices and demonstrated that hospitals have a positive influence on housing prices, indicating that the closer the proximity, the higher the housing prices.…”
Section: Variability In the Results Of The Influence Of Hospital Acce...mentioning
confidence: 99%
“…It concluded that hospitals have a positive influence on the price of surrounding houses. Liu et al (2022) compared the multi-scale effects of accessibility to various facilities on housing prices and demonstrated that hospitals have a positive influence on housing prices, indicating that the closer the proximity, the higher the housing prices.…”
Section: Variability In the Results Of The Influence Of Hospital Acce...mentioning
confidence: 99%
“…e house age, floor area ratio, and distance to subway stations commonly show negative effects [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…This observation of spatial heterogeneity is consistent with a recent study that suggested that residents of downtown and suburban areas may value different spatial characteristics [61]. With regard to schools as an influencing factor, the general view of previous studies is that all types of schools increase house prices in surrounding residential neighborhoods [62], while some scholars argue that only elementary and junior high schools are globally correlated with house prices [63], and there is also a recent study that used MGWR to analyze house prices in Wuhan and showed that only junior high schools and kindergartens are positively correlated, and elementary schools are negatively correlated [64]. The results of this paper differ from previous studies in that elementary schools and junior high schools are negatively correlated with house prices in high-house-price areas and are one of the main factors affecting the sale price of housing in the area: the closer to the school, the higher the house price.…”
Section: Spatial Distribution and Discrete Heterogeneity Of Commercia...mentioning
confidence: 99%